Detsa-Fëmijët (Kosovo 2000) - Moldoványi, Ferenc (Hungary : Engram Film Productions, 2001)
In the spring of 2000, Albanian children in Kosovska Mitrovica confess to the camera the deepest pain they have experienced in their short lives: being forced to witness their parents being brutally humiliated, tortured or killed. In some cases, children had to bury a parent themselves. The black-and-white photography, often shot with a hand-held and deliberately shaky camera, reveals the Apocalyptic reality of Kosovo: its devastated villages and half-destroyed houses, where some of the children are forced to live, seem to come straight from a futuristic horror movie. Now and then, color Super 8 images, filmed by the children themselves, since they are the only ones that can see their world as it really is, alternate with shots of the destroyed areas.
Duration: 01:30:00
Keywords: Documentary films